Why i trust my father? : in the eyes of malaysian adolescents - Jasmine Adela Mutang; Chan, Alfred, Huan Zhi; Norzihan Ayub; Chua, Bee Seok; Rosnah Ismail; Ooh, Siew Ling; Uichol Kim (World Academy of Science, Engineering and Technology, 2012)
This study aims to investigate how much both son and daughter trust their father and what are the underlying reasons they trust their father. The results revealed five main reasons why Malaysian adolescents trust their father. Those reasons are related to the role of father, father-child relationship, father’s characteristics, father’s nurturing nature and father’s attitude and behavior. A total of 1022 students (males = 241, females = 781) from one of public university in Sabah, Malaysia participated in the study. The participants completed open-ended questionnaires developed by Kim (2008), asking how much the adolescents trust their father, and the reasons why they trust their father. The data was analysed by using the indigenous psychology method proposed by [1] Findings of this study revealed the pattern of trust towards father for both Malaysian male and female adolescents. The results contributed new information about Malaysian adolescents’ trust towards their father form the indigenous context. The implications of finding will be discussed.